The Relationship of the Online Registration System Quality and the Effectiveness of Service Time with Patient Satisfaction - Suandari, Putu Vierda Lya; Nugraha, I Nyoman Adikarya; Sutrisnawati, Ni Nyoman Dwi (GLOBAL HEALTH SCIENCE GROUP, 2024)
The implementation of an online registration system is one of the efforts made by the Bali Mandara Eye Hospital to reduce the backlog of patients, The problem that often causes a buildup of patients in polyclinics is due to a lack of understanding of registering online. Over the last three years, the service time has the lowest score in the community satisfaction index report at the Bali Mandara Eye Hospital. This study aims to analyze the relationship between the quality of the online registration system and the effectiveness of service time, with patient satisfaction at the Bali Mandara Eye Hospital. This research uses a quantitative research approach using a questionnaire. The sampling technique in this research used cluster random sampling. Data was collected using a questionnaire with the sample participating in answering several questions in this research questionnaire. The sample for this research was patients who visited the Bali Mandara Eye Hospital polyclinic with a total sample of 96 samples. The analytical method used is multiple regression analysis. The online registration system quality variable is in the good category with average value is 2.78. The service time effectiveness variable is in the good category with average value is 2.80. The patient satisfaction variable has a satisfied category with average value is 2.96. The results of the analysis obtained a significance value for the F test, namely 0.001 < 0.05. These results mean that those two variables have a significant influence together on Patient Satisfaction. The coefficient of determination (R2) obtained was 0.869. This means that 86.9% of patient satisfaction is influenced by the Online Registration System Quality and Effectiveness of Service Time. The online registration system quality and the effectiveness of service times have a significant influence together on patient satisfaction at the Bali Mandara Eye Hospital.